Vanishing Heritage: An Analytical Study of the Oldest Tribal Jewelry Traditions of Telangana (Journal of Informatics Education and Research, 2025)
The state of Telangana, known for its rich cultural legacy, is home to several indigenous tribal communities whose jewelry represents an intricate synthesis of art, identity, and tradition. However, with the onset of modernization, commercialization, and migration, these age-old ornaments—once central to tribal aesthetics and socio-religious expression—are rapidly disappearing. This paper explores the oldest forms of tribal jewelry in Telangana, focusing on their materials, craftsmanship, and symbolic meaning. It further analyses the socio-economic and cultural factors responsible for their decline and examines the measures required for their preservation. Through qualitative ethnographic insights and secondary literature, the study reveals the deep cultural semiotics embodied in ornaments such as Nagaram, Tumbigalu, Guggu, and Kadiyamulu. The paper concludes that tribal jewelry, once a symbol of communal identity and cosmology, now faces extinction unless documented, revived, and integrated within heritage conservation frameworks.